INOVASI PEMBELAJARAN DI PESANTREN SALAF - Amrullah, Zen; Mutholingah, Siti (STAI Ma'had Aly Al-Hikam Malang, 2023)
Learning at the Pesantren Salaf is known as a learning system that uses traditional systems such as sorogan, bandongan, wetonan and tends not to use planned and systematically arranged learning tools. Therefore, even though the Pesantren Sidogiri is one of the pesantren salaf, this Islamic boarding school has learning innovations in the form of developing learning tools. The purpose of this research is to find out how the learning system is at the Pesantren Sidogiri and to find out how the learning innovations are at the Pesantren Sidogiri. This study used a qualitative approach with a descriptive research type. The results of this study are that the learning system at the Pesantren Sidogiri includes 2 systems, namely the Ma'hadiyah system and the Madrasiyah system. The learning innovations at the Pesantren Sidogiri include learning planning in the form of a syllabus designed by a special body called the Badan Tarbiyah wa al-Ta'lim Madrasy (BATARTAMA) and the implementation of innovations in the development of learning devices using a systems approach model. The findings of the systems approach model in the development of pesantren learning tools are at the same time a novelty in this research.